Determinants of failure to progress within 2 weeks of delivery: results of a multivariable analysis approach - José Morales-Roselló; Blanca Novillo-Del Álamo; Alicia Martínez-Varea (Elsevier, 2024)
Objective: The incidence of cesarean section (CS) for failure to progress (FP) has progressively increased; thus, knowing the factors that increase this incidence has become of crucial importance. This study aimed to find the true determinants of CS for FP within 2 weeks of delivery, proposing strategies to reduce its incidence. Material and Methods: A group of 957 term and late preterm (≥34 weeks) singleton pregnancies with a complete gestational follow-up and an ultrasound examination within 2 weeks of delivery were included in a retrospective observational study. Epidemiological, sonographic, and perinatal data were recorded, and multivariable logistic regression analyses were applied to create models to predict the importance of different variables in the explanation of FP. Results: Induction of labor was by far the most important modifiable factor, followed by smoking and maternal weight, while parity was the most important nonmodifiable factor, followed by maternal age and estimated fetal weight. The difference in days from the actual due date exerted no influence. Conclusions: To reduce the incidence of CS for FP, inductions of labor should be performed only under evidence-based medicine indications and kept to a minimum. In addition, maternal overweight reduction and maternal smoking cessation should be promoted before the initiation of gestation.